Seeing Is Believing: The CSI Effect Among Jurors in Malicious Wounding Cases - Call, Corey (2013)
With the popularization of television crime shows that focus heavily on forensic science, such as CSI and its spin-offs, concerns about a new threat to jury trials have emerged in recent years. Dubbed the “CSI effect,” this phenomenon has reportedly come to influence the way jurors perceive forensic evidence at trials based on the way forensic evidence is presented on television. While the CSI effect has been the topic of much discussion throughout the popular press, the CSI effect has seldom been empirically tested. In this study, we present a selection of media accounts as well as criminological and legal literature that provides a review of the current state of the CSI effect. Additionally, we present the findings of a survey of 60 jurors from five malicious wounding cases on the influence of viewing CSI on jury decision-making. Using a logistic regression model, we found that belief in the accuracy of the scientific methods used on CSI was significantly related to juror verdicts